Understanding Patient Navigation Functions: A Qualitative Exploration of Navigators’ Perspectives in Alberta, Canada - Sandra Berzins; Fedir Razumenko; Christine A Walsh; Karen L. Tang (Health Services Insights, 2026)
Background Patient navigation (PN) exemplifies a complex health intervention, involving multiple interacting components yet tailored to individual patient contexts and needs. Identifying functions and processes of complex interventions like PN enables a better understanding of how they are meant to work, moving beyond descriptions of program components such as tasks and services. With broad variation across programs, the navigator role can look quite different depending on context. Objective To explore the functions of PN from the perspective of patient navigators in Alberta, Canada. Design Qualitative descriptive approach. Methods Semi-structured interviews were conducted with patient navigators working in a range of patient-facing program types and settings across Alberta. Interviews were recorded and transcribed, then coded using NVivo 12 TM software. A thematic content analysis approach guided data analysis. Results We interviewed 29 navigators from a range of PN programs including cancer care, primary care networks, community agencies, and youth to adult transition. Nursing was the most common educational background of participants (n=12), followed by social work (n=9). Themes generated through thematic analysis highlighted three core functions of PN that collectively define its role as a complex, adaptive intervention: 1) creating a safety net for patients (theme 1), by addressing health and psychosocial needs (theme 1a) or by reducing barriers to care (theme 1b), 2) using advocacy and skill-building to enable patients to become more active participants in managing their health (theme 2), and 3) building relationships to strengthen patient trust and engagement (theme 3). Conclusions PN is a complex, multi-functional intervention that enhances patient care through relational, practical, and systemic support. Defining and understanding these key functions provides clarity and is critical for effective implementation and integration of PN into health systems and to inform future implementation and evaluation of PN programs in Canada.